Gaps in Perception on Social Media Use in Crisis Communication Between Vietnamese Organizations and Stakeholders - Tuong-Minh Ly-Le (Universitas Pelita Harapan, 2018)
Despite the emergence of social media in many aspects of Vietnamese lives, including marketing and promotional activities, Vietnamese organizations have used little social media in their crisis communication efforts. The organizations are hesitant to adopt social media in crisis communication and prefer to use traditional media because of its controllability and professionalism. However, with the increasing number of organizational crises that started on social media in the past years, it is arguably that Vietnamese stakeholders use social media as one of their main communication channels during crises. Should the organizations use social media in response? Through a series of interviews to PR practitioners and stakeholders in Vietnam, this research aims to find out the similarities and gaps in the perception of social media use for crisis communication between these two groups, and to guide a crisis communication practice that is appreciated by stakeholders. Bahasa Indonesia Abstrak: Meskipun munculnya media sosial dalam banyak aspek kehidupan Vietnam, termasuk kegiatan pemasaran dan promosi, organisasi Vietnam telah menggunakan sedikit media sosial dalam upaya komunikasi krisis mereka. Organisasi ragu-ragu untuk mengadopsi media sosial dalam komunikasi krisis dan lebih suka menggunakan media tradisional karena pengendalian dan profesionalisme. Namun, dengan meningkatnya jumlah krisis organisasi yang dimulai di media sosial dalam beberapa tahun terakhir, dapat dibilang bahwa pemangku kepentingan Vietnam menggunakan media sosial sebagai salah satu saluran komunikasi utama mereka selama krisis. Haruskah organisasi menggunakan media sosial sebagai jawaban? Melalui serangkaian wawancara kepada praktisi PR dan pemangku kepentingan di Vietnam, penelitian ini bertujuan untuk mengetahui persamaan dan kesenjangan dalam persepsi penggunaan media sosial untuk komunikasi krisis antara kedua kelompok ini, dan untuk memandu praktik komunikasi krisis yang dihargai oleh para pemangku kepentingan. .